Letramentos e produção textual: leitura e escrita de crônicas em ambientes mediados ou não por computadores - Pinheiro, Cinthia Maria da Conceição Bezerra (2015)
This research aims to create opportunities for students some moments of encouragement and improvement of writing skill, as well as (re)cognition of the characteristics of chronicle as a textual genre, producing it in mediated or non-mediated environment by digital technologies. This is a qualitative, descriptive and interventionist study, in which the method used is an experiment conducted through didactic sequences, divided into modules, with elementary students from the 8th grade from the Military Police School Rebeca Cristina Alves Simões, located in João Pessoa -PB. From a socio-discursive perspective and from everyday analysis, the purpose of this work is to collaborate with the students so that they can become increasingly competent and critic readers and writers. For its part, the intervention carried out in the classroom is based on the didactic sequence proposal presented by Schneuwly & Dolz (2004). For purposes of linguistics research, this study has as corpus 06 (six) textual productions, three carried out by students of the 8th graders A, which had made all the modules in an environment unmediated by computers, and the other three by 8th graders B, whose productions were developed in the school computer laboratory. These texts were analyzed considering the criteria proposed by Santos, Riche and Teixeira (2013) and Antunes (2006) for textual productions analysis, as well as the evaluation criteria of the chronicle genre used in the “Writing the Future” Portuguese Language Olympiad. During the analysis of the first textual production, it was possible to identify different problems related to the characteristic aspects of the textual genre and to the adaptation to standard Portuguese language. This analysis was performed on both aforementioned environments in order to support the development of modules, whatever didactic intervention in students’ writing process that, from then on, was being developed. After the intervention process made through the modules, it is possible to identify, in the final production of the 06 (six) investigated texts, that the difficulties previously detected in the first production were mostly overcome and that the environment in which the texts were produced (with and without computers mediation) did not interfere significantly to the success of production, but the computer-assisted environment was a motivating factor for many of the participating students. The studies of Schneuwly and Dolz (2004), about didactic sequences, the studies of Miller (2012), Bazerman (2011), Santos, Riche and Teixeira (2013), and Marcuschi (2008), among others, about textual genre analyses, and the studies of and the studies of Marcuschi and Xavier (2010), Gabriel (2013), Lévy (1993), Moran (2012) about the reflections on education and its digital technologies, were fundamental for this research.